Mutation in Mg-Protoporphyrin IX Monomethyl Ester (Oxidative) Cyclase Gene ZmCRD1 Causes Chlorophyll-Deficiency in Maize - Xue, Yingjie; Dong, Haixiao; Huang, Hongru; Li, Shipeng; Shan, Xiaohui; Li, He; Liu, Hongkui; Xia, Dong; Su, Shengzhong; Yuan, Yaping (Frontiers in Plant Science, 2022)
Chlorophyll molecules are noncovalently associated with chlorophyll-binding proteins to harvest light and perform charge separation vital for energy conservation during photosynthetic electron transfer in photosynthesis for photosynthetic organisms. The present study characterized a pale-green leaf (pgl) maize mutant controlled by a single recessive gene causing chlorophyll reduction throughout the whole life cycle. Through positional mapping and complementation allelic test, Zm00001d008230 (ZmCRD1) with two missense mutations (p.A44T and p.T326M) was identified as the causal gene encoding magnesium-protoporphyrin IX monomethyl ester cyclase (MgPEC). Phylogenetic analysis of ZmCRD1 within and among species revealed that the p.T326M mutation was more likely to be causal. Subcellular localization showed that ZmCRD1 was targeted to chloroplasts. The pgl mutant showed a malformed chloroplast morphology and reduced number of starch grains in bundle sheath cells. The ZmCRD1 gene was mainly expressed in WT and mutant leaves, but the expression was reduced in the mutant. Most of the genes involved in chlorophyll biosynthesis, chlorophyll degradation, chloroplast development and photosynthesis were down-regulated in pgl. The photosynthetic capacity was limited along with developmental retardation and production reduction in pgl. These results confirmed the crucial role of ZmCRD1 in chlorophyll biosynthesis, chloroplast development and photosynthesis in maize.